TANGGUNG JAWAB HUKUM PERAWAT TERHADAP KERUGIAN PASIEN DIKAITKAN DENGAN UNDANG - UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Maryam, Maryam (Katalogis, 2016)
The problem studied was how the legal accountablity of nurses and patients in axercising their rights and satisfying their obligations pursuant to Law Number 8 Year 1999 about Customer Pritection was. The purpose of theÂ research was to identity and analyze the right and obligations of the Protection. It was a normative juridical research based on Primary Legal Material, Secondary Legal Material and Tertiary Legal Material. It was concluded that the nurses were accountable to observe theÂ condition of patients, care the patients, dokument the health of patients, maintain the safety of patients, deliver services in accordance with nursing service standards, professional standards, stndards operation procedures, and prevailing law and regulations. The patients must supply with true information, be honest about their health status, follow advices given by doctors and nurses, respect all regulation effective in the health service facilities, pay charges and fees Â for health service rendered to them and exercise their right after satisfying their obligtions.